Análisis de las exportaciones del sector metalmecánica sobre el total de las exportaciones de la región Loreto, periodo 2018 – 2021 - Murayari Dosantos, Greti Betzabe (2024)
The thesis "Analysis of the exports of the metal-mechanical sector on the total exports of the Loreto region, period 2018-2021", aims to analyze the evolution of exports of this sector. This study took as its methodology the descriptive correlational type of research, of non-experimental design. The research population and sample group included all metallurgical exports registered with SUNAT - CUSTOMS for the period in question. Consequently, the results show that the FOB export value of the metalworking industry of the Loreto region in the period 2018-2021 has a downward trend, characterized by a decrease of 33%, while the value in kilograms increases erratically, characterized by a growth rate of 17%, especially in the period 2019-2020. The countries of destination were in the first instance Kazakhstan, in second position the Netherlands and third Colombia, while the most exported products were "nuclear reactors, boilers, machinery, apparatus and mechanical appliances; parts of such machinery or apparatus, articles of iron or steel", which both account for more than 96%. Finally, the companies that managed to export products in this sector were Helicópteros del Sur SA, which had a higher FOB value of US$ 1,811,664, in second place, Petrex SA, with an FOB value of US$ 795,831, both representing 84%.